2016
DOI: 10.1002/ppp.1924
|View full text |Cite
|
Sign up to set email alerts
|

Soil Physical and Environmental Conditions Controlling Patterned-Ground Variability at a Continuous Permafrost Site, Svalbard

Abstract: This study examines soil physical and environmental conditions controlling patterned‐ground variability on an alluvial fan in a continuous permafrost landscape, at Adventdalen, Svalbard. On‐site monitoring of ground temperature, soil moisture and snow depth, laboratory analyses of soil physical properties and principal component analysis indicate that the distribution of patterned ground depends primarily on soil texture, soil moisture and the winter ground thermal regime associated with snow cover. Mudboils a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…The role of rims as preferential outlets of subsurface heat is consistent with the idea that topographic highs in ice wedge polygons cool more efficiently than depressed areas (Christiansen, 2005;Gamon et al, 2012;Watanabe et al, 2017), but conflicts with the idea previously suggested by Lachenbruch (1966), that rim development gradually suppresses ice wedge cracking by increasing snow entrapment in the troughs. It is important to acknowledge that our model does not fully negate Lachenbruch's hypothesis, as conditions not incorporated into the sensitivity analysis, such as vegetation differences between the rims and center, can also influence snow accumulation patterns and energy exchange between the ground and atmosphere (Gamon et al, 2012).…”
Section: Sensitivity Of Ice Wedge Temperatures To Topographysupporting
confidence: 67%
See 1 more Smart Citation
“…The role of rims as preferential outlets of subsurface heat is consistent with the idea that topographic highs in ice wedge polygons cool more efficiently than depressed areas (Christiansen, 2005;Gamon et al, 2012;Watanabe et al, 2017), but conflicts with the idea previously suggested by Lachenbruch (1966), that rim development gradually suppresses ice wedge cracking by increasing snow entrapment in the troughs. It is important to acknowledge that our model does not fully negate Lachenbruch's hypothesis, as conditions not incorporated into the sensitivity analysis, such as vegetation differences between the rims and center, can also influence snow accumulation patterns and energy exchange between the ground and atmosphere (Gamon et al, 2012).…”
Section: Sensitivity Of Ice Wedge Temperatures To Topographysupporting
confidence: 67%
“…This conclusion is supported by prior field studies. In Svalbard, for example, Christiansen (2005) suggested that most of the cooling experienced by an ice wedge occurs through the rims, and Watanabe et al (2017) observed that ice wedge cracking is most active in polygons with well-developed rims hosting minimal snow cover. Along the Beaufort Sea coast in northwestern Canada, it has been observed that ice wedges beneath well-developed troughs crack infrequently, presumably due to the insulation provided by increased snow cover (Mackay, 2000;Burn, 2004).…”
Section: Sensitivity Of Ice Wedge Temperatures To Topographymentioning
confidence: 99%
“…The ice‐wedge research site is located on the outermost part of a large late Holocene alluvial fan in the Adventdalen valley, central Svalbard (Figure a). Adventdalen is a broad U‐shaped valley surrounded by flat‐top, 800–900 m high mountains composed of sedimentary rocks of Early Permian to Eocene age.…”
Section: The Studied Ice‐wedge Sitementioning
confidence: 99%
“…The polygons occur mainly as quadrangles, pentagons and hexagons with an average diameter of about 20 m and three‐way junctions (Figure ). The surface morphology shifts into small polygons (< 3 m in diameter), earth hummocks and mudboils toward the loess‐free area higher on the fan …”
Section: The Studied Ice‐wedge Sitementioning
confidence: 99%
“…Although individual pattern types have some common features, which allow classification based on morphology and/or site characteristics (e.g. Treml et al , ; Feuillet et al , ; Watanabe et al , ), high variability of shape and size results from a wide range of environmental settings in which they develop (see Goldthwait, ; Washburn, ; Grab, ). Such variability makes it difficult to draw specific conclusions from a purely binary‐data approach.…”
Section: Introductionmentioning
confidence: 99%